Green Accounting Disclosures and Financial Performance of Non–Financial Companies in Nigeria - Adedipe Oluwaseyi Ayodele; Oladeji Ige Olubunmi; Olayiwola Michael Adeyemi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The effectiveness and efficiency of an organization are evaluated based on its social, environmental, and financial contributions, as recognized by the community and the environment in which it operates. However, there has been inconclusive and inconsistence in the existing literature on whether Green Accounting Disclosures have a positive or negative effect on financial performance and previous literature measured the financial performance with profitability and lack of transparency in reporting environmental impact in the company’s annual report. Hence, there is a need to examine the effects of Green Accounting Disclosures (GAD) on the Financial Performance of manufacturing companies in Nigeria to provide better comprehensive insights into manufacturing companies’ performance. The study deployed stakeholder theory and longitudinal research design. The population comprised all manufacturing companies in Nigeria and a stratified sampling technique was used to select forty -five (45) samples of the companies for the study. Secondary data was collected from the annual reports and analyzed using multiple regression. The results of the fixed effect estimation revealed that Tobin q has a t-stat of 0.299 and, a p of 0.031. This indicates that positive GAD contributes significantly to the effective communication and strategic implementation of sustainable practices. Furthermore, the study explored the moderating role of board characteristics, particularly Gender Diversity, in shaping the relationship between GAD and financial performance